2005
DOI: 10.1038/ncb1244
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-localized GAP for Cdc42 functions downstream of ARF1 to control Arp2/3 complex and F-actin dynamics

Abstract: The small GTP-binding ADP-ribosylation factor 1 (ARF1) acts as a master regulator of Golgi structure and function through the recruitment and activation of various downstream effectors. It has been proposed that members of the Rho family of small GTPases also control Golgi function in coordination with ARF1, possibly through the regulation of Arp2/3 complex and actin polymerization on Golgi membranes. Here, we identify ARHGAP10--a novel Rho GTPase-activating protein (Rho-GAP) that is recruited to Golgi membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
176
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 31 publications
11
176
0
4
Order By: Relevance
“…The identity of GEFs that might activate Cdc42 at the Golgi remains unknown. However, a recent study identified a Golgiassociated Cdc42 GAP protein, ARHGAP21, which is recruited to Golgi membranes through a direct interaction between Arf1-GTP and a region of ARHGAP21 encompassing the PH domain and an adjacent helical motif [20]. The PH domain of ARHGAP21 does not bind phospholipids, and it therefore appears that Golgi recruitment is mediated primarily through its interaction with Arf1.…”
Section: Arf Regulation Of Actin Assembly In the Golgimentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of GEFs that might activate Cdc42 at the Golgi remains unknown. However, a recent study identified a Golgiassociated Cdc42 GAP protein, ARHGAP21, which is recruited to Golgi membranes through a direct interaction between Arf1-GTP and a region of ARHGAP21 encompassing the PH domain and an adjacent helical motif [20]. The PH domain of ARHGAP21 does not bind phospholipids, and it therefore appears that Golgi recruitment is mediated primarily through its interaction with Arf1.…”
Section: Arf Regulation Of Actin Assembly In the Golgimentioning
confidence: 99%
“…Intriguingly, it was shown recently that Arf1, ARHGAP21 and Cdc42 also act in concert to promote the clathrin-independent endocytosis of cholesterol-rich micro-domains at the plasma membrane ( Figure 1b) [22], indicating that the Arf1-ARHGAP21 complex acts at multiple sites within the cell. It should be noted that, although originally reported as ARHGAP10, the protein described in studies [20] and [21] has been renamed ARHGAP21 (accession # NP_065875) to avoid confusion with a previously existing ARHGAP10 protein (NP_078881), also known as GRAF2 (GTPase regulator associated with focal adhesion kinase 2) (P. Chavrier, personal communication).…”
Section: Arf Regulation Of Actin Assembly In the Golgimentioning
confidence: 99%
“…Moreover, a role for actin dynamics is strongly suggested by the involvement of some actin cytoskeleton regulatory molecules and actin-binding or actin-associated proteins in the formation and/or movement of transport intermediates. Those include Cdc42 and some downstream signalling effectors such as N-WASP, Arp2/3, and LIMK1 [Erickson et al, 1996;Fucini et al, 2002;Luna et al, 2002;Carreno et al, 2004;Chen et al, 2004a;Matas et al, 2004;Rosso et al, 2004], Cdc42-GAP protein [Dubois et al, 2005], the Cdc42-related protein TC10 [Kanzaki et al, 2002], mAbp1 [Fucini et al, 2002;Kessels and Qualmann, 2002], non-muscle myosin II [Heimann et al, 1999;Duran et al, 2003], Golgi-specific spectrin and ankyrin isoforms [Beck et al, 1994[Beck et al, , 1997Deverajan et al, 1996], the spectrin family member syne-1 [Gough et al, 2003[Gough et al, , 2004, syndapins Qualmann, 2002, 2004], the Sla2/Huntingtin-interactin protein 1 member Hip1R [Carreno et al, 2004] and cortactin [Cao et al, 2005]. Collectively, these data indicate that a complex molecular machinery regulates actin dynamics in Golgi membranes, which seems to be involved in Golgi-associated transport events.…”
Section: Introductionmentioning
confidence: 99%
“…ARHGAP21 is an effector of Arf1 at the Golgi, and is also a GAP for Cdc42 (Dubois et al, 2005;Ménétrey et al, 2007). Arf GEFs (notably cytohesins and EFA6) and Arf GAPs also interact with Rho-family G proteins and other actin cytoskeleton regulators (Myers and Casanova, 2008;Randazzo et al, 2007).…”
Section: Arf Regulation Of the Actin Cytoskeletonmentioning
confidence: 99%